Variability in depth-mediated shifts in methanogen and methanotroph communities across tropical Andean mountain peatlands - Angela Lafuente; Louis J. Lamit; Rodney A. Chimner; John Hribljan; Nathan Basiliko; Juan C. Benavides; Erik A. Lilleskov (Pedobiologia, 2025)

Rapid riparian ecosystem decline in Rocky Mountain National Park - David J. Cooper; E. William Schweiger; Jeremy R. Shaw; Cherie J. Westbrook; Kristen Kaczynski; Hanem Abouelezz; Scott M. Esser; Koren Nydick; Isabel de Silva; Rodney A. Chimner (Conservation Biology, 2025)
Understanding the drivers of ecosystem collapse is critical for resource management, particularly for protected areas mandated to preserve biodiversity. In Rocky Mountain National Park, Colorado, tall willows ( Salix spp.) dominated riparian vegetation, and a beaver–willow state was the natural ecosystem type in the Colorado River headwaters. However, willows comprise a portion of elk diets and are a preferred food for recently introduced moose, and the vegetation structure has changed dramatically since the early 2000s. To assess ecosystem changes, we analyzed time‐series data on willow height from 1997 to 2021 inside and outside 3 exclosures built to exclude ungulates, area of tall willows in 1999 and 2019, area of open water from 1953 to 2019, vegetation composition in 1998 and 2021, groundwater depth from 1996 to 2021, surface water flow from 1953 to 2023, and climate from 1950 to 2023. Tall willow coverage and open water area declined by >90% from 1999 to 2019. Willow height outside the ungulate exclosures declined by more than 75% since the 1990s; yet, within exclosures that were formerly browsed, willow height increased by up to 500%. Tall willow communities have largely been replaced by grasslands. Browsing by elk and moose likely played a pivotal role in triggering a collapse of the beaver–willow state and the formation of an alternative moose–elk–grassland state that appears stable and may be difficult to reverse without direct human action. Restoration efforts will depend on a reduction in herbivory and reconnection of the river with its floodplain.

Mapping the distribution and condition of mountain peatlands in Colombia for sustainable ecosystem management - Patrick Nicolás Skillings-Neira; Juan C. Benavides; Michael J. Battaglia; Rodney A. Chimner; Laura Bourgeau-Chavez; Craig Wayson; Randall Kolka; Erik A. Lilleskov (Journal of Environmental Management, 2025)

Characterizing northern white-cedar communities in harvested and unharvested lowland forests of Michigan, USA - Robin Michigiizhigookwe Clark; Christopher R. Webster; Laura S. Kenefic; Christel C. Kern; Rodney A. Chimner (Wetlands Ecology and Management, 2024)

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Elevation and temperature are strong predictors of long-term carbon accumulation across tropical Andean mountain peatlands - John A. Hribljan; Moira Hough; Erik A. Lilleskov; Esteban Suarez; Katherine Heckman; Ana Maria Planas-Clarke; Rodney A. Chimner (Mitigation and Adaptation Strategies for Global Change, 2024)

Fire History and Long-Term Carbon Accumulation in Hemi-boreal Peatlands - Dominic M. Uhelski; Evan S. Kane; Katherine A. Heckman; Rodney A. Chimner (Ecosystems, 2023)

Characterization of Vernal Pools Across National Parks in the Great Lakes Region - Samantha R. Kurkowski; Laura L. Bourgeau-Chavez; Michael J. Battaglia; Dorthea J.L. Vander Bilt; Rodney A. Chimner (Wetlands, 2023)

Evaluation and improvement of the E3SM land model for simulating energy and carbon fluxes in an Amazonian peatland - Fenghui Yuan; Daniel M. Ricciuto; Xiaofeng Xu; Daniel T. Roman; Erik Lilleskov; Jeffrey D. Wood; Hinsby Cadillo-Quiroz; Angela Lafuente; Jhon Rengifo; Randall Kolka; Lizardo Fachin; Craig Wayson; et al. (Agricultural and Forest Meteorology, 2023)

Evidence for older carbon loss with lowered water tables and changing plant functional groups in peatlands - Julia E. M. Stuart; Colin L. Tucker; Erik A. Lilleskov; Randall K. Kolka; Rodney A. Chimner; Katherine A. Heckman; Evan S. Kane (Global Change Biology, 2023)
A small imbalance in plant productivity and decomposition accounts for the carbon (C) accumulation capacity of peatlands. As climate changes, the continuity of peatland net C storage relies on rising primary production to offset increasing ecosystem respiration (ER) along with the persistence of older C in waterlogged peat. A lowering in the water table position in peatlands often increases decomposition rates, but concurrent plant community shifts can interactively alter ER and plant productivity responses. The combined effects of water table variation and plant communities on older peat C loss are unknown. We used a full‐factorial 1‐m 3 mesocosm array with vascular plant functional group manipulations (Unmanipulated Control, Sedge only, and Ericaceous only) and water table depth (natural and lowered) treatments to test the effects of plants and water depth on CO 2 fluxes, decomposition, and older C loss. We used Δ 14 C and δ 13 C of ecosystem CO 2 respiration, bulk peat, plants, and porewater dissolved inorganic C to construct mixing models partitioning ER among potential sources. We found that the lowered water table treatments were respiring C fixed before the bomb spike (1955) from deep waterlogged peat. Lowered water table Sedge treatments had the oldest dissolved inorganic 14 C signature and the highest proportional peat contribution to ER. Decomposition assays corroborated sustained high rates of decomposition with lowered water tables down to 40 cm below the peat surface. Heterotrophic respiration exceeded plant respiration at the height of the growing season in lowered water table treatments. Rates of gross primary production were only impacted by vegetation, whereas ER was affected by vegetation and water table depth treatments. The decoupling of respiration and primary production with lowered water tables combined with older C losses suggests that climate and land‐use‐induced changes in peatland hydrology can increase the vulnerability of peatland C stores.

Plant functional types drive Peat Quality differences - Dominic M. Uhelski; Evan S. Kane; Rodney A. Chimner (Wetlands, 2022)

Challenges and opportunities for restoration of high-elevation Andean peatlands in Ecuador - Esteban Suarez; Segundo Chimbolema; Ricardo Jaramillo; Leo Zurita-Arthos; Paul Arellano; Rodney A. Chimner; John S. Stanovick; Erik A. Lilleskov (Mitigation and Adaptation Strategies for Global Change, 2022)
Páramo peatlands are a regional reservoir of biodiversity and ecosystem services, accumulating large amounts of carbon and buffering water flows. Despite their importance, they have a long history of use and impacts including drainage for agriculture and grazing, and water withdrawal for human uses. Here we present a preliminary assessment of the conservation status of páramo peatlands in Ecuador and, using a case study, discuss peatland restoration as a tool for mitigation and adaptation to the impacts of current climate change. Through a simple index assessing the cumulative presence of signs of human activities on 163 peatland sites, we found that the level of impact was higher for peatlands located in the Western branch of the cordillera, whereas current human population density, precipitation, and elevation were not significant predictors of the levels of impact. Also, starting in 2017, we implemented a pilot restoration initiative on a 21-ha peatland which had been drained and converted into pasture for at least 150 years. The restoration consisted of two ditch blocking techniques implemented to stop fast-moving water and promote the rewetting of the peatland. During the next 3 years, water table increased from 27 ± 3 cm below the soil surface to 7 ± 1 cm by 2021, while wetland plant communities are colonizing and closing the pools in the blocked ditches. Re-wetting of the peatland has led to an increase in the abundance of native species. This case study suggests that restoration initiatives are an efficient and cost-effective approach to a better management of páramo peatlands, with high potential as a tool for mitigation and adaptation to climate change.

Peatland microbial community responses to plant functional group and drought are depth‐dependent - Louis J. Lamit; Karl J. Romanowicz; Lynette R. Potvin; Jay T. Lennon; Susannah G. Tringe; Rodney A. Chimner; Randall K. Kolka; Evan S. Kane; Erik A. Lilleskov (Molecular Ecology, 2021)
Peatlands store one‐third of Earth's soil carbon, the stability of which is uncertain due to climate change‐driven shifts in hydrology and vegetation, and consequent impacts on microbial communities that mediate decomposition. Peatland carbon cycling varies over steep physicochemical gradients characterizing vertical peat profiles. However, it is unclear how drought‐mediated changes in plant functional groups (PFGs) and water table (WT) levels affect microbial communities at different depths. We combined a multiyear mesocosm experiment with community sequencing across a 70‐cm depth gradient, to test the hypotheses that vascular PFGs (Ericaceae vs. sedges) and WT (high vs. low) structure peatland microbial communities in depth‐dependent ways. Several key results emerged. (i) Both fungal and prokaryote (bacteria and archaea) community structure shifted with WT and PFG manipulation, but fungi were much more sensitive to PFG whereas prokaryotes were much more sensitive to WT. (ii) PFG effects were largely driven by Ericaceae, although sedge effects were evident in specific cases (e.g., methanotrophs). (iii) Treatment effects varied with depth: the influence of PFG was strongest in shallow peat (0–10, 10–20 cm), whereas WT effects were strongest at the surface and middle depths (0–10, 30–40 cm), and all treatment effects waned in the deepest peat (60–70 cm). Our results underline the depth‐dependent and taxon‐specific ways that plant communities and hydrologic variability shape peatland microbial communities, pointing to the importance of understanding how these factors integrate across soil profiles when examining peatland responses to climate change.

Arbuscular mycorrhizal inoculation has similar benefits to fertilization for Thuja occidentalis L. seedling nutrition and growth on peat soil over a range of pH: implications for restoration - Guswarni Anwar; Erik A. Lilleskov; Rodney A. Chimner (New Forests, 2020)

Mapping Mountain Peatlands and Wet Meadows Using Multi-Date, Multi-Sensor Remote Sensing in the Cordillera Blanca, Peru - Rodney A. Chimner; Laura Bourgeau-Chavez; Sarah Grelik; John A. Hribljan; Ana Maria Planas Clarke; Molly H. Polk; Erik A. Lilleskov; Beatriz Fuentealba (Wetlands, 2019)

Is Indonesian peatland loss a cautionary tale for Peru? A two-country comparison of the magnitude and causes of tropical peatland degradation - Erik Lilleskov; Kevin McCullough; Kristell Hergoualc’h; Dennis del Castillo Torres; Rodney Chimner; Daniel Murdiyarso; Randy Kolka; Laura Bourgeau-Chavez; John Hribljan; Jhon del Aguila Pasquel; Craig Wayson (Mitigation and Adaptation Strategies for Global Change, 2019)

Multidate, multisensor remote sensing reveals high density of carbon‐rich mountain peatlands in the páramo of Ecuador - John A. Hribljan; Esteban Suarez; Laura Bourgeau‐Chavez; Sarah Endres; Erik A. Lilleskov; Segundo Chimbolema; Craig Wayson; Eleanor Serocki; Rodney A. Chimner (Global Change Biology, 2017)
Tropical peatlands store a significant portion of the global soil carbon (C) pool. However, tropical mountain peatlands contain extensive peat soils that have yet to be mapped or included in global C estimates. This lack of data hinders our ability to inform policy and apply sustainable management practices to these peatlands that are experiencing unprecedented high rates of land use and land cover change. Rapid large‐scale mapping activities are urgently needed to quantify tropical wetland extent and rate of degradation. We tested a combination of multidate, multisensor radar and optical imagery (Landsat TM / PALSAR / RADARSAT ‐1/ TPI image stack) for detecting peatlands in a 2715 km 2 area in the high elevation mountains of the Ecuadorian páramo. The map was combined with an extensive soil coring data set to produce the first estimate of regional peatland soil C storage in the páramo. Our map displayed a high coverage of peatlands (614 km 2 ) containing an estimated 128.2 ± 9.1 Tg of peatland belowground soil C within the mapping area. Scaling‐up to the country level, páramo peatlands likely represent less than 1% of the total land area of Ecuador but could contain as much as ~23% of the above‐ and belowground vegetation C stocks in Ecuadorian forests. These mapping approaches provide an essential methodological improvement applicable to mountain peatlands across the globe, facilitating mapping efforts in support of effective policy and sustainable management, including national and global C accounting and C management efforts.

Multi-decadal Changes in Water Table Levels Alter Peatland Carbon Cycling - Rodney A. Chimner; Thomas G. Pypker; John A. Hribljan; Paul A. Moore; James M. Waddington (Ecosystems, 2017)

Peatland carbon stocks and accumulation rates in the Ecuadorian páramo - John A. Hribljan; Esteban Suárez; Katherine A. Heckman; Erik A. Lilleskov; Rodney A. Chimner (Wetlands Ecology and Management, 2016)

Artificial microtopography and herbivory protection facilitates wetland tree (Thuja occidentalis L.) survival and growth in created wetlands - Laura C. Kangas; Rose Schwartz; Michael R. Pennington; Christopher R. Webster; Rodney A. Chimner (New Forests, 2016)

Biogeochemical Research Priorities for Sustainable Biofuel and Bioenergy Feedstock Production in the Americas - Hero T. Gollany; Brian D. Titus; D. Andrew Scott; Heidi Asbjornsen; Sigrid C. Resh; Rodney A. Chimner; Donald J. Kaczmarek; Luiz F. C. Leite; Ana C. C. Ferreira; Kenton A. Rod; Jorge Hilbert; Marcelo V. Galdos; et al. (Environmental Management, 2015)

Grazing intensity levels influence C reservoirs of wet and mesic meadows along a precipitation gradient in Northern Patagonia - Andrea Soledad Enriquez; Rodney A. Chimner; María Victoria Cremona; Paula Diehl; Griselda Luz Bonvissuto (Wetlands Ecology and Management, 2015)

Effects of water table position and plant functional group on plant community, aboveground production, and peat properties in a peatland mesocosm experiment (PEATcosm) - Lynette R. Potvin; Evan S. Kane; Rodney A. Chimner; Randall K. Kolka; Erik A. Lilleskov (Plant and Soil, 2015)

Developing and Evaluating Rapid Field Methods to Estimate Peat Carbon - Rodney A. Chimner; Cassandra A. Ott; Charles H. Perry; Randall K. Kolka (Wetlands, 2014)

Long-term water table manipulations alter peatland gaseous carbon fluxes in Northern Michigan - Drew M. Ballantyne; John A. Hribljan; Thomas G. Pypker; Rodney A. Chimner (Wetlands Ecology and Management, 2014)

Temperature and Microtopography Interact to Control Carbon Cycling in a High Arctic Fen - Patrick F. Sullivan; Seth J. T. Arens; Rodney A. Chimner; Jeffrey M. Welker (Ecosystems, 2008)

A Tropical Freshwater Wetland: II. Production, Decomposition, and Peat Formation - Rodney A. Chimner; Katherine C. Ewel (Wetlands Ecology and Management, 2005)

CO 2 exchange in three Canadian High Arctic ecosystems: response to long‐term experimental warming - Jeffrey M. Welker; Jace T. Fahnestock; Greg H. R. Henry; Kevin W. O'Dea; Rodney A. Chimner (Global Change Biology, 2004)
Carbon dioxide exchange, soil C and N, leaf mineral nutrition and leaf carbon isotope discrimination (LCID‐Δ) were measured in three High Arctic tundra ecosystems over 2 years under ambient and long‐term (9 years) warmed (∼2°C) conditions. These ecosystems are located at Alexandra Fiord (79°N) on Ellesmere Island, Nunavut, and span a soil water gradient; dry, mesic, and wet tundra. Growing season CO 2 fluxes (i.e., net ecosystem exchange (NEE), gross ecosystem photosynthesis (GEP), and ecosystem respiration ( R e )) were measured using an infrared gas analyzer and winter C losses were estimated by chemical absorption. All three tundra ecosystems lost CO 2 to the atmosphere during the winter, ranging from 7 to 12 g CO 2 ‐C m −2 season −1 being highest in the wet tundra. The period during the growing season when mesic tundra switch from being a CO 2 source to a CO 2 sink was increased by 2 weeks because of warming and increases in GEP. Warming during the summer stimulated dry tundra GEP more than R e and thus, NEE was consistently greater under warmed as opposed to ambient temperatures. In mesic tundra, warming stimulated GEP with no effect on R e increasing NEE by ∼10%, especially in the first half of the summer. During the ∼70 days growing season (mid‐June–mid‐August), the dry and wet tundra ecosystems were net CO 2 ‐C sinks (30 and 67 g C m −2 season −1 , respectively) and the mesic ecosystem was a net C source (58 g C m −2 season −1 ) to the atmosphere under ambient temperature conditions, due in part to unusual glacier melt water flooding that occurred in the mesic tundra. Experimental warming during the growing season increased net C uptake by ∼12% in dry tundra, but reduced net C uptake by ∼20% in wet tundra primarily because of greater rates of R e as opposed to lower rates of GEP. Mesic tundra responded to long‐term warming with ∼30% increase in GEP with almost no change in R e reducing this tundra type to a slight C source (17 g C m −2 season −1 ). Warming caused LCID of Dryas integrafolia plants to be higher in dry tundra and lower in Salix arctic plants in mesic and wet tundra. Our findings indicate that: (1) High Arctic ecosystems, which occur in similar mesoclimates, have different net CO 2 exchange rates with the atmosphere; (2) long‐term warming can increase the net CO 2 exchange of High Arctic tundra by stimulating GEP, but it can also reduce net CO 2 exchange in some tundra types during the summer by stimulating R e to a greater degree than stimulating GEP; (3) after 9 years of experimental warming, increases in soil carbon and nitrogen are detectable, in part, because of increases in deciduous shrub cover, biomass, and leaf litter inputs; (4) dry tundra increases in GEP, in response to long‐term warming, is reflected in D. integrifolia LCID; and (5) the differential carbon exchange responses of dry, mesic, and wet tundra to similar warming magnitudes appear to depend, in part, on the hydrologic (soil water) conditions. Annual net ecosystem CO 2 ‐C exchange rates ranged from losses of 64 g C m −2 yr −1 to gains of 55 g C m −2 yr −1 . These magnitudes of positive NEE are close to the estimates of NPP for these tundra types in Alexandra Fiord and in other High Arctic locations based on destructive harvests.

Differences in carbon fluxes between forested and cultivated micronesian tropical peatlands - Rodney A. Chimner; Katherine C. Ewel (Wetlands Ecology and Management, 2004)

Soil respiration rates of tropical peatlands in Micronesia and Hawaii - Rodney A. Chimner (Wetlands, 2004)

Using stable oxygen isotopes to quantify the water source used for transpiration by native shrubs in the San Luis Valley, Colorado U.S.A. - Rodney A. Chimner; David J. Cooper (Plant and Soil, 2004)

Modeling carbon accumulation in Rocky Mountain fens - Rodney A. Chimner; David J. Cooper; William J. Parton (Wetlands, 2002)